2018
DOI: 10.1007/s00122-018-3150-2
|View full text |Cite
|
Sign up to set email alerts
|

Complete resistance to powdery mildew and partial resistance to downy mildew in a Cucumis hystrix introgression line of cucumber were controlled by a co-localized locus

Abstract: Key message A single recessive gene for complete resistance to powdery mildew and a major-effect QTL for partial resistance to downy mildew were co-localized in a Cucumis hystrix introgression line of cucumber. Downy mildew (DM) and powdery mildew (PM) are two major foliar diseases in cucumber. DM resistance (DMR) and PM resistance (PMR) may share common components; however, the genetic relationship between them remains unclear. IL52, a Cucumis hystrix introgression line of cucumber which has been reported to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 60 publications
0
47
0
Order By: Relevance
“…Previous studies showed that most of the QTLs for PM resistance in cucumber are recessively inherited [6,7,34], indicating that the resistance is governed by impaired susceptibility (S) genes [12,13] mapped cucumber genes that are homolog to know plant S genes for PM and downy mildew (DM) resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that most of the QTLs for PM resistance in cucumber are recessively inherited [6,7,34], indicating that the resistance is governed by impaired susceptibility (S) genes [12,13] mapped cucumber genes that are homolog to know plant S genes for PM and downy mildew (DM) resistance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, The MLO-like gene CsaMLO8 [13] located nearby pmG5.4 [15]. A DMR and PMR candidate gene Csa5M622830 (Chr.5: 24735193
 24738505) was also nearby the pmG5.4 [34]. The candidate gene Csa5G604340 for pmG5.3 is a homology of AtPMR6 [13].…”
Section: Discussionmentioning
confidence: 99%
“…One hundred and forty-five F 2 populations (B/S population) were generated from the cross between 'EC1' and '8419s-1' [15]. One hundred and fifty-five RILs population (O/S population) were derived from the cross of 'CCMC' and 'IL52' [16]. 'EC1' is an inbred line derived from a European type 'Delta star' [15], which bear blunt round fruit tip with fruit tip index in range of 2.873±0.110 and fruit tip angel in range of 151°±7° ( Fig.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…IL52 is an introgression line derived from interspecific hybridization between cucumber and the wild relative species Cucumis hystrix Chakr. [16,[42][43][44], which bear oval round fruit tip with fruit tip index in range of 2.441±0.047 and fruit tip angel in range of 127°±4° (Fig. 2B, Additional file 1: Table S1).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…one bulk has more allele A while the other bulk has more allele a. BSA was primarily used to develop genetic markers for detecting gene-trait association at its early stage (1,2). Application of the next generation sequencing (NGS) technology to BSA eliminated the time-consuming and labor-intensive marker development and genetic mapping steps, and dramatically sped up the detection of gene-trait associations (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). This technique was termed either QTL-seq or BSA-Seq in different publications (5,6,19), we adapted the latter here because it can be applied to study both qualitative and quantitative traits.…”
Section: Introductionmentioning
confidence: 99%